Effect of heat treatment temperature on microstructure and electromagnetic shielding properties of graphene/SiBCN composites. Issue 12 (December 2019) - Wei, Yue; Yongsheng, Liu; Mingxi, Zhao; Fang, Ye; Laifei, Cheng
Abstract: Three-dimensional (3D) graphene/SiBCN composites (GF/SiBCN) were prepared by depositing SiBCN ceramics in 3D graphene foam via the chemical vapor infiltration technique. The effect of the heat treatment temperature on the microstructure, phase composition, and electromagnetic properties of the GF/SiBCN composite was investigated. The SiBCN ceramics maintained an amorphous structure in the composite below 1400 °C above which the crystallinity of the free carbon phase gradually increased. While the Si3 N4 and B4 C phases started to crystallize at 1500 °C and their crystallinity increased with temperature, SiC was observed at 1700 °C. The electromagnetic shielding effectiveness of GF/SiBCN increased with the heat treatment temperature.